The Structure and Catalytic Activity of Pt Complexes Heterogenized on a Silica Surface - Vitaly K. Yatsimirsky; Lyudmila A. Belyakova; Lyudmila P. Oleksenko; Ol'ga Yu. Boldyreva (Adsorption Science & Technology, 2000)
The catalytic activity of complex compounds containing different metal contents immobilized on a silica surface towards the oxidation of carbon monoxide and hydrogen has been investigated. In addition, the influence of the concentration of hydrogen and oxygen and the treatment of such catalysts by the individual components in the reaction mixture on their catalytic activity in the hydrogen oxidation reaction has also been studied. The structural peculiarities of platinum complexes heterogenized on a silica surface have been established by diffuse reflectance electronic spectroscopy.